Neutrophil to lymphocyte ratio, platelet to lymphocyte ratio, and monocyte to lymphocyte ratio in ADHD: a systematic review and meta-analysis - Adam Gędek; Adam Gędek; Szymon Modrzejewski; Marta Gędek; Marta Gędek; Anna Z. Antosik; Paweł Mierzejewski; Monika Dominiak (Frontiers in Psychiatry, 2023)
IntroductionAttention-deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder with an unclear etiology. Systemic inflammation and immune dysregulation may play a role in the pathogenesis of ADHD. Morphology-derived parameters such as neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and monocyte to lymphocyte ratio (MLR), have been proposed as peripheral biomarkers of the immune-inflammatory process in various diseases. However, studies examining their role in ADHD remain inconclusive.MethodsA systematic review and a meta-analysis were conducted to evaluate the association between NLR, MLR, PLR and ADHD. Relevant articles were identified, screened, and assessed for quality according to PRISMA guidelines. Moreover, a qualitative and quantitative analyses were performed.ResultsThe review contained eight eligible studies, five of which were included in the meta-analysis. The meta-analysis showed that ADHD patients had higher NLR and PLR values compared to health controls. No significant difference in MLR value was observed between the two groups. Analysis in relation to ADHD subtypes showed no significant differences in inflammatory markers in any of the included studies as well. The influence of medical treatment on these ratios could not be adequately assessed due to limited data.ConclusionADHD patients exhibit higher NLR and PLR than healthy controls, which may indicate the potential immune-inflammatory involvement in this disorder. Further studies on inflammatory markers and ADHD, especially those considering the impact of treatment and clinical symptoms, are essential to comprehensively understand this association.